Hope and life satisfaction among Chinese shadow education tutors: The mediating roles of positive coping and perceived social support - Ji, Jie; Zhou, Linzhi; Wu, Yunpeng; Zhang, Mohan (Frontiers in Psychology, 2022)
The relationship between hope and life satisfaction has been studied, leaving the underlying mechanism of how hope predicts life satisfaction unexplored. Using a cross-sectional design, this study investigated two potential mediators in the relationship between hope and life satisfaction among a sample of Chinese shadow education institution (SEI) tutors who may under immense professional development pressure. A total of 221 SEI tutors participated in the online survey and reported their hope, positive coping, perceived social support, and life satisfaction. Results indicated that positive coping mediated the relationship between hope and life satisfaction. Results also supported the hypothesized serial mediating effect of positive coping and perceived social support. Tutors with high level of hope tend to adopt positive coping strategies, thus will receive more social support, which lead to the life satisfaction improvement. These findings revealed the independent and accumulative mediating effects of positive coping and perceived social support on the relationship between hope and life satisfaction, and had implications for the psychological intervention of SEI tutors who are currently facing enormous industry pressure.